Stigmatization, discrimination and illness - Bohle, Leah Franziska (Universitätsverlag Göttingen, 2013)
"She was given her own plate, her own cup, everything of her own, even when she just touched a cloth then nobody wanted to touch it again." (Halima, HIV-seropositive) The book sheds light on the profound influence of an HIV-seropositive diagnosis on the lives of women and their social environment in the United Republic of Tanzania. The author, a medical doctor and social anthropologist, tells the story of six Tanzanian HIV-seropositive women, focusing on their negotiation and perception of illness and disease. Furthermore, the high levels of discrimination and stigmatization in the context of HIV-seropositivity that they experience are presented in detail, weaving together the impacts of an HIV-seropositive diagnosis with results analyzed both from a Medical Anthropology and Public Health perspective. Despite a new era of antiretroviral treatment, available in Tanzania free of cost, that has given cause for hope in a change in how the disease is perceived, the book impressively underlines that being HIV-seropositive remains a great challenge and heavy burden for women in Tanzania.